2018
DOI: 10.18203/2319-2003.ijbcp20180095
|View full text |Cite
|
Sign up to set email alerts
|

Study of drug utilization pattern and adverse drug reactions of psychotropic drugs in psychiatric inpatient department of tertiary care hospital

Abstract: Background: Mental disorders are now widely recognized as a major contributor to the global burden of disease. The drug use in psychiatric illness is a complex process and because of this the optimal benefits of drug therapy in patient care is not achieved. This often leads to increased cost of medical care, drug resistance, adverse effects and patient mortality. Hence, this study is undertaken to study the drug utilization pattern and adverse drug reactions of psychotropic drugs in psychiatric inpatient depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…Antipsychotics was the commonest group and olanzapine was the most common psychotropic drug suspected of causing ADRs in current study. This finding matched with the study conducted by Gurung et al (2018). Tremors (extrapyramidal symptoms) was the most common ADR observed due to psychotropic drugs in present study, which is in line with the findings reported by Prajapati et al (2013) and Gurung et al (2018).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Antipsychotics was the commonest group and olanzapine was the most common psychotropic drug suspected of causing ADRs in current study. This finding matched with the study conducted by Gurung et al (2018). Tremors (extrapyramidal symptoms) was the most common ADR observed due to psychotropic drugs in present study, which is in line with the findings reported by Prajapati et al (2013) and Gurung et al (2018).…”
Section: Discussionsupporting
confidence: 94%
“…This finding matched with the study conducted by Gurung et al (2018). Tremors (extrapyramidal symptoms) was the most common ADR observed due to psychotropic drugs in present study, which is in line with the findings reported by Prajapati et al (2013) and Gurung et al (2018). In present study, among the patients who had ADRs due to psychotropic drugs, the number of patients with causality assessment of ADRs as "possible" was more compared to the number of patients who had causality as "probable".…”
Section: Discussionsupporting
confidence: 92%
“… 24 Amantadine or propranolol were prescribed to these patients to provide relief from tremors. In contrast to these findings, a study conducted by Gurung et al 11 observed EPS as the most common ADR followed by sedation. This difference in the findings could be due to the difference in the prescribing pattern of psychotropic medications.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies also indicate the same. 11 14 In our study population, maximum ADRs were observed because of atypical antipsychotics. The prescription pattern also revealed that the majority of patients received antipsychotics across all diagnostic categories.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation